A description of interventions promoting healthier ready-to-eat meals (to eat in, to take away, or to be delivered) sold by specific food outlets in England: a systematic mapping and evidence synthesis. (December 2017) - Hillier-Brown, Frances; Summerbell, Carolyn; Moore, Helen; Wrieden, Wendy; Adams, Jean; Abraham, Charles; Adamson, Ashley; Araújo-Soares, Vera; White, Martin; Lake, Amelia
Abstract Background Ready-to-eat meals (to eat in, to take away or to be delivered) sold by food outlets are often more energy dense and nutrient poor compared with meals prepared at home, making them a reasonable target for public health intervention. The aim of the research presented in this paper was to systematically identify and describe interventions to promote healthier ready-to-eat meals (to eat in, to take away, or to be delivered) sold by specific food outlets in England. Methods A systematic search and sift of the literature, followed by evidence mapping of relevant interventions, was conducted. Food outlets were included if they were located in England, were openly accessible to the public and, as their main business, sold ready-to-eat meals. Academic databases and grey literature were searched. Also, local authorities in England, topic experts, and key health professionals and workers were contacted. Two tiers of evidence synthesis took place: type, content and delivery of each intervention were summarised (Tier 1) and for those interventions that had been evaluated, a narrative synthesis was conducted (Tier 2). Results A total of 75 interventions were identified, the most popular being awards. Businesses were more likely to engage with cost neutral interventions which offered imperceptible changes to price, palatability and portion size. Few interventions involved working upstream with suppliers of food, the generation of customer demand, the exploration of competition effects, and/or reducing portion sizes. Evaluations of interventions were generally limited in scope and of low methodological quality, and many were simple assessments of acceptability. Conclusions Many interventions promoting healthier ready-to-eat meals (to eat in, to take away, or to be delivered) sold by specific food outlets in England are taking place; award-type interventions are the most common. Proprietors of food outlets in England that, as their main business, sell ready-to-eat meals, can be engaged in implementing interventions to promote healthier ready-to-eat-food. These proprietors are generally positive about such interventions, particularly when they are cost neutral and use a health by stealth approach.